Effect of Azo-Class Food Additive Tartrazine on Tooth Development in Mice (Journal of Bio-Science, 2026)
Tartrazine (Tz) is a chemically synthesized food dye that is being used widely as a coloring agent in different foods. Growing pieces of evidence are reporting that these food additives are genotoxic. Since colored foods are particularly attractive to children, they are the most vulnerable to the adverse effects of food additives. Thus, this study was designed to elucidate the effect of Tz on tooth development in mice models. For this study, we administered Tz at 0.75 mg/Kg, 1.5 mg/Kg, and 3.0 mg/Kg intraperitoneally into two-week-old mice for 14 consecutive days. Then, the mice were euthanized, and mandibles were separated for removing molar (M) teeth and collecting tissue samples from the jaw. We assessed expressions of Adipoq, Bsp, Nqo1, and Sirt6 genes by polymerase chain reaction (PCR) in the tissue samples and measured the size of molar 1 (M1), molar 2 (M2), and molar 3 (M3) tooth. While there was no noticeable change in length, we observed that M3 tooth became thinner in Tz treated animal. Similarly, mice body weight was decreasing dose dependently, with a significant decline at the highest dose. Additionally, Bsp and Sirt6 gene expression were enhanced in Tz administration in mice. Overall, our data indicates that Tz has a negative effect on tooth development, and further research is needed for elucidating its mechanism of action.J. Bio-Sci. 33(1): 13-20, 2025